Equatorial Ionospheric Disturbance Field‐Aligned Plasma Drifts Observed by C/NOFS. Issue 5 (18th May 2018) - Zhang, Ruilong; Liu, Libo; Balan, N.; Le, Huijun; Chen, Yiding; Zhao, Biqiang
Abstract: Using C/NOFS satellite observations, this paper studies the disturbance field‐aligned plasma drifts in the equatorial topside ionosphere during eight geomagnetic storms in 2011–2015. During all six storms occurred in the solstices, the disturbance field‐aligned plasma drift is from winter to summer hemisphere especially in the morning‐midnight local time sector and the disturbance is stronger in June solstice. The two storms occurred at equinoxes have very little effect on the field‐aligned plasma drift. Using the plasma temperature data from DMSP satellites and Global Positioning System‐total electron content, it is suggested that the plasma density gradient seems likely to cause the disturbance winter‐to‐summer plasma drift while the role of plasma temperature gradient is opposite to the observed plasma drift. Key Points: Seasonal dependence of disturbance field‐aligned plasma drift in the equatorial topside ionosphere is presented Disturbance field‐aligned plasma drift is from winter to summer hemisphere Conjugate asymmetry of plasma density gradient seems likely to cause the disturbance winter‐to‐summer plasma drift